Public versus Private Education in Hawaii - Espiritu, Antonina (Education Policy Analysis Archives, 2001)
This study presents a time-series evidence on the timing and degree of feedback relationship between participation in education and income growth in Hawaii. Using the unrestricted vector autoregression approach and two related measures of linear dependence and feedback, the results suggest that across all educational levels, i.e., K-12 and tertiary, participation in public education could be a good predictor of income growth in Hawaii. However, decomposing the feedback effect by frequency suggests that the dominance of public education over private education in explaining the variation in income growth to be concentrated mainly on the short-run to medium-run for tertiary level and long-run to permanent effect for K-12 level. Hawaii state legislature and educators should perhaps take these results as a motivation not to ignore the problems plaguing Hawaii's public schools but should work towards greater improvement and support for public education given its predicted significant overall contribution to the Hawaiian economy.